Eletrofloculação seguido pela adição de Moringa oleifera para o tratamento de efluentes de lagoa de vinhaça - NATAL, Jean Paulo Silva (2016)
With the industrial advance, the generation of liquid effluents has grown considerably. The inappropriate disposal of this waste can prejudice the health of the human beings and the environmental quality. The sugar and alcohol sector, for example, is responsible for the generation of a big quantity of liquid effluents, called vinasse, which has significant quantity of organic material, low pH, high corrosivity and high indexes of biochemical oxygen demand (DBO5). Being that, the general objective of this project consists in using a electroflocculation tecnique together with usage of the seeds of Moringa oleifera in the treatment of effluents from vinasse ponds. It was used in the step of electroflocculation, the factorial planning 3 2. As a method of anaylsis, in this step, it was evaluated the influence of parameters: Time and intensity of a eletric chain through the values of total organic carbon reduction (COT) and DBO5. In the next step the seed powder of M. oleifera was evaluated in different quantities. As parameters for the evaluation of efficiency of the process of turbidity values, total organic carbon COT and DBO5 were used. It has been established as the best condition of operation for the electroflocculation step with the combination of time and intensity of a electric chain in 90 minutes and 1 ampere (A). The step of electroflocculation presented a reduction of 72% COT, 36 % DBO5 and 92 % of turbidity. The next step, where different quantities of M. oleifera’s seed powder were added, it was obtained different results, the best condition of the operation was the addition of 0,5 g.L-1 of degreased Moringa’s seed powder where it was obtained a reduction of 70 % DBO5 and 81% in turbidity. However for the parameter COT none of the samples presented satisfactory results, due to the increase of organic material through the seeds of M. oleifera in effluent. When evaluating the general efficiency process (electroflocculation allied with the usage of the seeds) it was verified for the evaluated parameters COT, DBO5 and turbidity a significant reduction of 38 %, 80 % e 90 % respectively. It was concluded that the usage of the electroflocculation tecnique allied to the usage of degreased M. oleifera’s seeds is a clean alternative and with big potencial for the treatment of vinasse effluents.